2013
DOI: 10.1177/1538574413500723
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of the Common Femoral Artery for Limb Ischemia

Abstract: These novel data demonstrate that eCFR is a durable treatment for patients with limb ischemia associated with CFA disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 20 publications
1
34
1
Order By: Relevance
“…Cumulatively, wound haematoma occurred in 24 of 269 procedures (5·5 (95 per cent c.i. 0·2 to 17·2) per cent; 4 studies), similar to 35 of 1154 in the endarterectomy group (3·9 (1·7 to 6·9) per cent; 7 studies). No wound infection or lymph leak was reported in the endovascular group.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Cumulatively, wound haematoma occurred in 24 of 269 procedures (5·5 (95 per cent c.i. 0·2 to 17·2) per cent; 4 studies), similar to 35 of 1154 in the endarterectomy group (3·9 (1·7 to 6·9) per cent; 7 studies). No wound infection or lymph leak was reported in the endovascular group.…”
Section: Resultsmentioning
confidence: 78%
“…Only ten studies collected data prospectively, of which five reported endovascular intervention and five reported CFE. Less than half of the studies (11 of 28) had a sample size of greater than 100 and follow‐up of 1 year or more, of which four were in the endovascular group and seven were in the CFE group ( Table S6 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When combined with provisional stenting for suboptimal technical results, PTA is the most commonly used technique in the treatment of femoral popliteal disease. Review of the literature for CFA lesions treated with PTA alone reveals primary patency rates from 59% to 88% at 1 year and at 83% at 2 years . Available data on longer‐term patency of PTA for CFA lesions are more limited, describing primary patency rates of 66% and 60% at 4 and 5 years, respectively .…”
Section: Endovascular Therapies To Cfa Disease and Evidence For Theirmentioning
confidence: 99%